Pengaruh Kepemimpinan Transformasional Dan Kepuasan Kerja Terhadap Kinerja Guru MTsN 8 Blitar - Sulistyowati, Sulistyowati; Mulyaningtyas, Ratna Dewi (Universitas Islam Kadiri, 2024)
Teachers have a very important role in the continuity of learning in schools, as well as the success in implementing the curriculum in schools. Teacher performance is influenced by many factors, there needs to be teacher motivation to carry out active, creative and innovative tasks. The Principal plays an important role in determining the success of achieving the Vision and Mission in the school. The presence of a leader can help an organization smoothly achieve its goals and success. Leaders at MTs Negeri 8 Blitar use a transformational leadership style, which leads to the process of building a commitment towards organizational goals and giving confidence to followers to achieve these goals. Job satisfaction has quite a big influence on improving teacher performance so that efforts to improve performance are carried out through increasing job satisfaction. The higher the job satisfaction, the higher the teacher's performance. This research is quantitative research conducted at MTs N 8 Blitar by distributing research questionnaires to 35 teachers as respondents. The tool for analyzing data is SPSS. The results of data processing prove that the variable indicators have met the validity and reliability tests. Transformational leadership and job satisfaction variables have a significant influence on teacher performance.